Corporate Image as a Differentiation Strategy in Healthcare: A Study in the COVID-19 Crisis Period in Turkey - Esra Fener; Tuncay Köse (SAGE Open)
This study aims to examine the protective and positive effects of corporate image in healthcare services from the perspective of Porter’s General Competitive Strategies. The COVID-19 pandemic has been a crisis period in which healthcare organizations struggle to eliminate infectious diseases and face economic difficulties. During this crisis period, the sustainability of private healthcare organizations in a competitive environment has become uncertain. Considering this difficulty, the investigation of competitive strategies that healthcare organizations can implement is an important issue that has been neglected. In this context, the study examined the positive effects of corporate image on patient satisfaction and loyalty. The data of this cross-sectional and descriptive study were collected from 446 participants in Istanbul. Three scales—corporate image scale, patient satisfaction scale, and patient loyalty scale—were used to model the concept, and the AMOS structural equation model was applied. The findings show the positive effects of corporate image on patient satisfaction and loyalty. In addition, the effect of corporate image on patient loyalty increases through patient satisfaction. Therefore, corporate image serves as a differentiation strategy that healthcare institutions can implement in normal competitive conditions and in times of crisis. Hospital managers are advised to give importance to corporate image studies and develop them positively. The positive corporate image of healthcare institutions can play a proactive and protective role both in times of crisis and in normal competitive conditions.